Mushaf Bahriyah - Mustopa Mustopa; Zainal Arifin Madzkur (Lajnah Pentashihan Mushaf Al-Qur'an, 2020)
Bahriyah Mushaf is decided to be one the Indonesian Standard Qur’an to facilitate the pupil of the Qur’an or people memorizing the Qur’an. The corner system of the mushaf gives the easiness in memorizing the Qur’an. It is through the field study and literature, known that the Bahriyah Mushaf as a standard mushaf has not had a good response from society. This can be observed in the lack of the publishers which publish this mushaf. The Publisher of Menara Kudus printed the Bahriyah Mushaf model but it cannot be included into the Bahriyah Standard Mushaf because it did not follow the points standardized by the Ministry of Religious Affairs. However, the Bahriyah Mushaf by Menara Kudus is the most used in the pesantren (Islamic boarding schools) to memorize the Qur’an, because the pesantren network and its distribution have already been established well. In line with the rampant publication of the Usmani Standard Mushaf using the corner system that becomes the character of Bahriyah, this Standard Mushaf is losing its role more and more since the main character of this mushaf has been adopted to the Usmani Standard Mushaf. The imla’i rules which are mostly used in this mushaf, even add the problems in the Bahriyah Standard Mushaf.